Image Segmentation Using Hardware Forest Classifiers - Pittman, Neil; Forin, Alessandro; Criminisi, Antonio; Shotton, Jamie; Mahram, Atabak (2013 Field-Programmable Custom Computing Machines, 2013)
Image segmentation is the process of partitioning an image into segments or subsets of pixels for purposes of further analysis, such as separating the interesting objects in the foreground from the un-interesting objects in the background. In many image processing applications, the process requires a sequence of computational steps on a per pixel basis, thereby binding the performance to the size and resolution of the image. As applications require greater resolution and larger images the computational resources of this step can quickly exceed those of available CPUs, especially in the power and thermal constrained areas of consumer electronics and mobile. In this work, we use a hardware tree-based classifier to solve the image segmentation problem. The application is background removal (BGR) from depth-maps obtained from the Microsoft Kinect sensor. After the image is segmented, subsequent steps then classify the objects in the scene. The approach is flexible: to address different application domains we only need to change the trees used by the classifiers. We describe two distinct approaches and evaluate their performance using the commercial-grade testing environment used for the Microsoft Xbox gaming console.